REVITALIZING TRADITIONAL METAL CRAFTS: A KNOWLEDGE TRANSFER EMPOWERING SUSTAINABILITY THROUGH BIOMIMICRY DESIGN - Ahmad, Syed Mohd Faisal Syed; Khairi, Hanif; Legino, Rafeah (Kantor Bahasa Kalimantan Timur, 2025)
This paper aims to empower biomimicry design through knowledge transfer for the sustainability of traditional Malay metal crafts, particularly in Malaysia. Recent studies have highlighted a regression in the acceptance and practice of cherished local skills, focusing on the dying art of metalware and jewellery. The primary objective of this project is to ensure the continued practice of metalsmithing by seamlessly integrating traditional craftsmanship with contemporary technological trends by implementing a comprehensive knowledge transfer targeting Malaysia's youth. The concept of